(untitled) (Baghdad Science Journal, 2011)
Pot experiment was carried out at the College of Agriculture – Baghdad University during autumn season, 2007. Thirteen treatments were formulated to evaluate the effectiveness of four applications of Phosphorus (0, 60, 60×2 and 120 Kg P. h-1) and three applications of Zinc (0, 25×2 mg Zn. L-1 and 50 mg Zn. Kg soil-1) along with inoculating seeds of bean with strains mixture 889 and 1865 and non-inoculated treatment, on nodulation, yield and protein content in seeds (N%). The results showed that inoculated plants exceeded on non-inoculated one in all the studied characteristics. While, P and Zn, applications at the rate of 60×2 kg/ha and 25×2 mg/L respectively, significantly, increased, nodulation, yield, protein content in seeds of bean compared to non-inoculated treatment and Control. The highest grain yield (28.86 g/plant) were obtained with the interaction treatment (60×2 kg P /ha + 25×2 mg Zn /L) with Rhizobium inoculation. So, combined application of Rhizobium inoculant along with 60×2 kg P /ha and 25×2 mg Zn /L was considered to be the suitable combination of fertilizer for inoculated bean cultivation in silty clay loam soils.